All Theater Is Revolutionary Theater - Bennett, Benjamin, 1939- (Book collections on Project MUSE., 2005)
All Theater Is Revolutionary Theater is the first book to consider why, in the Western tradition (and only in the Western tradition), theatrical drama is regarded as its own literary or poetic type, when the criteria needed to differentiate drama from other forms of writing do not resemble the criteria by which types of prose or verse are ordinarily distinguished. Through close readings of such playwrights as Beckett, Brecht, Büchner, Eliot, Shaw, Wedekind, and Robert Wilson, Benjamin Bennett looks at the relationship between literature and drama, identifying typical problems in the development of dramatic literature and exploring how the uncomfortable association with theatrical performance affects the operation of drama in literary history.Bennett's historical investigations into theoretical works ranging from Aristotle to Artaud, Brecht, and Diderot suggest that the attempt to include drama in the system of Western literature causes certain specific incongruities that, in his view, have the salutary effect of preserving the otherwise endangered possibility of a truly liberal, progressive, or revolutionary literature.